2019
DOI: 10.1088/1757-899x/546/5/052075
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Inflation and Money Supply using Spatial Vector Autoregressive Model with Calendar Variation: Restricted vs Non-restricted Coefficient

Abstract: One of the tasks of the government is to maintain price stability reflected in the stability of inflation through the regulation of the money supply. Therefore the government needs to know the forecast of the inflation rate and the money supply. In modeling inflation and the money supply simultaneously in Indonesia, three things need to be accommodated, namely the relationship between variables, the existence of space-time relationships and the effect of Eid al-Fitr. The spatial vector autoregressive model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another variant of the VAR model that has been used to model inflation and money supply is the Spatial Vector Autoregression (SVAR) model. Nonrestricted SVAR models have been found to have better predictive power than restricted ones (Sumarminingsih, Suharsono, Ruchjana, & Stiawan, 2019). Additionally, research using VAR has been conducted to investigate the explanatory power of bank credit on inflation rates in Jordan, and it was concluded that there is a positive effect of bank credit on the inflation rate (Al-Oshaibat & Banikhalid, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another variant of the VAR model that has been used to model inflation and money supply is the Spatial Vector Autoregression (SVAR) model. Nonrestricted SVAR models have been found to have better predictive power than restricted ones (Sumarminingsih, Suharsono, Ruchjana, & Stiawan, 2019). Additionally, research using VAR has been conducted to investigate the explanatory power of bank credit on inflation rates in Jordan, and it was concluded that there is a positive effect of bank credit on the inflation rate (Al-Oshaibat & Banikhalid, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%